Penilaian Estetika Jalan Kota untuk Mendukung Pariwisata Berkelanjutan Kota Sambas - Delyanet, Delyanet; Pawa, Janiarto Paradise (Media Wisata, 2024)
Commitment to tourism development encouraging the local government of Sambas to build and improve accessibility to and from tourist attractions. Without taken it into account properly, the aesthetics of the road can decrease and in the long term, it can downturn the tourism business. This research was conducted to support sustainable tourism in Sambas City, especially from an aesthetic perspective. The research was carried out using quantitative methods using Scenic Beauty Estimation (SBE) and Semantic Differentiation (SD). The research results showed that the SBE scores were mostly in the medium category (46%), while the SD results showed little difference with the SBE results. Comparison with sustainable road elements shows that the local government needs to improve the road area to make it sustainable.